The Use of Digital Evidence in Law Enforcement Efforts in Human Trafficking Cases - Djamadi, Noval; W. Badu, Lisnawaty; Towadi, Mellisa (Estudiante Law Journal, 2025)
This study aims to determine the efforts of law enforcement in using digital evidence to prove human trafficking cases in Indonesia. This study is a normative study analyzed descriptively qualitatively. The results of the study indicate that law enforcement efforts in utilizing digital evidence include digital data seizures, electronic communication tracking, digital financial transaction analysis, and the involvement of digital forensic experts in authenticating evidence submitted to the court. Although the national legal framework, such as the ITE Law and Law Number 21 of 2007, has recognized the validity of digital evidence, its implementation in the field still faces various obstacles both in terms of technical, regulatory, and human resources. Law enforcement officers still need to increase their capacity in handling digital evidence professionally and proportionally